Improving Students' Proposal Writing Abilities Through Flowcharts - Rina Octavia Simarmata; Nurhayati Sitorus; Fenty Debora Napitupulu (STABN RADEN WIJAYA WONOGIRI, 2021)
This study looks into how well flowcharts might help students write proposals. Students frequently struggle with structuring ideas, maintaining coherence, and adhering to methodical processes when drafting proposals. Flowcharts were used as a visual planning tool to help students navigate the stages of proposal development, including problem identification, objectives, technique, and anticipated results, in order to solve these problems. The study used a pre-test and post-test approach with students who were taught through activities based on flowcharts. Organization, clarity, and overall writing quality increases were measured by analyzing data gathered through writing exams. The results show that using flowcharts greatly improved students' capacity for idea generation, logical proposal structure, and cohesive information presentation. The study advises including flowcharts into writing training after concluding that they are an excellent teaching method for enhancing students' proposal writing abilities